The Role of Sodium Bicarbonate in the Management of Some Toxic Ingestions. (8th August 2017) - Mirrakhimov, Aibek E.; Ayach, Taha; Barbaryan, Aram; Talari, Goutham; Chadha, Romil; Gray, Adam
Abstract : Adverse reactions to commonly prescribed medications and to substances of abuse may result in severe toxicity associated with increased morbidity and mortality. According to the Center for Disease Control, in 2013, at least 2113 human fatalities attributed to poisonings occurred in the United States of America. In this article, we review the data regarding the impact of systemic sodium bicarbonate administration in the management of certain poisonings including sodium channel blocker toxicities, salicylate overdose, and ingestion of some toxic alcohols and in various pharmacological toxicities. Based on the available literature and empiric experience, the administration of sodium bicarbonate appears to be beneficial in the management of a patient with the above-mentioned toxidromes. However, most of the available evidence originates from case reports, case series, and expert consensus recommendations. The potential mechanisms of sodium bicarbonate include high sodium load and the development of metabolic alkalosis with resultant decreased tissue penetration of the toxic substance with subsequent increased urinary excretion. While receiving sodium bicarbonate, patients must be monitored for the development of associated side effects including electrolyte abnormalities, the progression of metabolic alkalosis, volume overload, worsening respiratory status, and/or worsening metabolic acidosis. Patients with oliguric/anuric renal failure and advanced decompensated heart failure should not receive sodium bicarbonate.